Technology Entrepreneurship (ENT600) : Todak Culture Sdn Bhd / Muhammad Daniel Firdaus Abd Majid - Abd Majid, Muhammad Daniel Firdaus (2021)
This is an attempt to know how the theories can be applied to the practical situation. As a student in UiTM Arau, it is a part of study for everyone to undergo a case study project. I got an opportunity to do some research about a company business strategy and services in the real situation. The general information about the company has been collected and the information is gathered through the primary and secondary source as well. Objective of this case study project is to work on the background, organizational structure and services that Todak Culture Sdn Bhd provided. I also study on the business, marketing and operational strategy that this company has been implemented for years. In this case study, I also analyse the strength, weaknesses, opportunity and threats of the company and product by using SWOT analysis. Thus, from the feedback and needs from the existing customers of this company, I analysed and find a solution to overcome the existing problem from that product and to fulfil their customer’s needs.